Creative Thinking Ability of Biology Teachers at State Senior High Schools in Pekanbaru - Febblina Daryanes; Riki Apriyandi Putra (STAI Hubbulwathan Duri, 2022)
The teacher is one of the determinants of success in the learning process and the formation of the soft skills and hard skills of the students. If a teacher has the ability to think creatively and make decisions with a focus on improving higher-order thinking and is consistent over time, it is likely to be successful in training students' creative thinking skills. This study aims to analyze the level of creative thinking skills of Biology teachers at SMA Negeri Pekanbaru City. The population in this study were all Biology teachers in Pekanbaru City Senior High School, amounting to 62 people. The sampling technique used was saturated sampling. Data was collected using questionnaires and interview guidelines, the questionnaire was compiled based on 4 indicators of creative thinking developed by Marzano. The questionnaire data was analyzed by calculating the percentage and then interpreted into several categories, while the results of the interviews were analyzed qualitatively. The results showed that the level of creative thinking skills of Biology teachers in Pekanbaru City High School was 81.35%. The indicator of creative thinking ability, namely